A study of multiple Felis catus papillomavirus types (1, 2, 3, 4) in cat skin lesions in Italy by quantitative PCR. Issue 8 (August 2018) - Mazzei, Maurizio; Forzan, Mario; Carlucci, Vito; Anfossi, Antonio G; Alberti, Alberto; Albanese, Francesco; Binanti, Diana; Millanta, Francesca; Baroncini, Lisa; Pirone, Andrea; Abramo, Francesca
Objectives: The aim of the study was to investigate, by quantitative PCR (qPCR), the presence of papillomavirus in feline viral plaques (VPs), Bowenoid in situ carcinoma (BISC), squamous cell carcinoma (SCC) and actinic keratosis (AK). Methods: Twenty-nine cases with previously established diagnoses of feline VPs, BISC, invasive SCC and AK were selected from a dermatopathological database. A critical re-evaluation of diagnosis was performed by defining clear criteria toward carcinomatous vs non-carcinomatous, in situ vs invasive (if carcinomatous) and viral vs actinic. Cases were evaluated for p16 immunolocalisation. The presence of the target viral genes for Felis catus papillomavirus (FcaPV)-1, FcaPV-2, FcaPV-3 and FcaPV-4 was determined by qPCR. The data generated ΔΔCq values, which represent a normalised measure of DNA viral quantity. Samples with a positive ΔΔCq value were submitted to sequence analysis. Results: Four VPs, 19 BISCs, four SCCs and one case of AK were included. By ΔΔCq analysis we found that all VPs were positive for FcaPV-1 or FcaPV-2; eight BISCs were positive for FcaPV-1, FcaPV-2 and FcaPV-4. FcaPV-2 was the most prevalent among the group of VPs and BISCs. Conclusions and relevance: Using the ΔΔCq method we report the first evidence of FcaPV-1, FcaPV-2 and FcaPV-4 in Italy. FcaPV-2 was the most frequently detected; to a lesser extent, FcaPV-1 and FcaPV-4 were detected in the examined samples. FcaPV-3 was never associated with viral-induced lesions by ΔΔCq investigation. Compared with conventional PCR the ΔΔCq method has the advantage of establishing a possible role of the virus in the outcome of infection.